2015
DOI: 10.7314/apjcp.2015.16.16.7219
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Profile of De Novo B lineage Acute Lymphoblastic Leukemia: Determination of Frequency, Distribution Pattern and Identification of Rare and Novel Chromosomal Aberrations in Indian Patients

Abstract: Background: Chromosomal aberrations identified in acute lymphoblastic leukemia (ALL) have an important role in disease diagnosis, prognosis and management. Information on karyotype and associated clinical parameters are essential to physicians for planning cancer control interventions in different geographical regions. Materials and Methods: In this study, we present the overall frequency and distribution patterns of chromosomal aberrations in both children and adult de novo B lineage ALL Indian patients using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…8 25 26 However, a few Indian studies have reported lower 27 28 29 30 and higher incidences. 9 10 Our data on E2A–PBX1 fusion incidence are also comparable to the majority of Western and Chinese data. 12 13 16 The mean total leukocyte count in this subgroup was significantly high compared with the overall mean.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…8 25 26 However, a few Indian studies have reported lower 27 28 29 30 and higher incidences. 9 10 Our data on E2A–PBX1 fusion incidence are also comparable to the majority of Western and Chinese data. 12 13 16 The mean total leukocyte count in this subgroup was significantly high compared with the overall mean.…”
Section: Discussionsupporting
confidence: 86%
“…Hyperdiploidy was the most common numerical chromosomal abnormality (8.4%), which was comparable with studies in India and China. 9 10 11 However, the incidence of hyperdiploidy in Iran, the US, and Europe is significantly higher, ranging from 25.4% in the US to as high as 39% in France. 12 13 14 15 16 The reported incidence of hyperdiploidy in Central and South America is varied ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, after consulting many studies, we selected ARID5B rs10821936,6,15–17 GATA3 rs3824662,8,18–20 IKZF1 rs4132601,1,21–24 and PIP4K2A rs708831825–27 to determine whether these associations are generally applicable in Chinese children. To the best of our knowledge, no study has examined the effects of these SNPs on ALL in China.…”
mentioning
confidence: 99%